2015
DOI: 10.1128/iai.00918-15
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Adaptation In Vivo in Response to a High-Salt Diet

Abstract: e Helicobacter pylori exhibits a high level of intraspecies genetic diversity. In this study, we investigated whether the diversification of H. pylori is influenced by the composition of the diet. Specifically, we investigated the effect of a high-salt diet (a known risk factor for gastric adenocarcinoma) on H. pylori diversification within a host. We analyzed H. pylori strains isolated from Mongolian gerbils fed either a high-salt diet or a regular diet for 4 months by proteomic and whole-genome sequencing me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 59 publications
0
27
0
Order By: Relevance
“…The transcriptional changes described in this study presumably enhance the ability of the bacteria to tolerate these changes. In addition to short-term transcriptional alterations in response to changes in salt concentration, a recent study revealed proteomic and genomic changes in H. pylori strains isolated from Mongolian gerbils fed a high-salt diet for 4 months (56). Thus, high-salt stress can lead to the adaptation and selection of H. pylori strains with enhanced fitness for growth in a high-salt environment.…”
Section: Figmentioning
confidence: 99%
“…The transcriptional changes described in this study presumably enhance the ability of the bacteria to tolerate these changes. In addition to short-term transcriptional alterations in response to changes in salt concentration, a recent study revealed proteomic and genomic changes in H. pylori strains isolated from Mongolian gerbils fed a high-salt diet for 4 months (56). Thus, high-salt stress can lead to the adaptation and selection of H. pylori strains with enhanced fitness for growth in a high-salt environment.…”
Section: Figmentioning
confidence: 99%
“…Moreover, 3% salt was added to the drinking water to enhance H. pylori colonization (44,45). After 2 weeks, PCR, RUT, and bacterial culture experiments were carried out to examine the infection status of H. pylori.…”
Section: Methodsmentioning
confidence: 99%
“…Mutagenesis of the ؉59 DNA motif in H. pylori strain PZ5056. To evaluate the effect of the ϩ59 DNA sequences on cagA expression, unmarked mutations were introduced upstream of the cagA open reading frame (ORF) using a previously described counterselection protocol involving a cat-rpsL cassette (41)(42)(43)(44). Briefly, streptomycin-resistant mutants were generated by transforming H. pylori strain PZ5056 with a nonreplicating plasmid containing a cloned H. pylori rpsL gene harboring a lysine-to-arginine mutation at codon 43 of rpsL (42,44).…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the effect of the ϩ59 DNA sequences on cagA expression, unmarked mutations were introduced upstream of the cagA open reading frame (ORF) using a previously described counterselection protocol involving a cat-rpsL cassette (41)(42)(43)(44). Briefly, streptomycin-resistant mutants were generated by transforming H. pylori strain PZ5056 with a nonreplicating plasmid containing a cloned H. pylori rpsL gene harboring a lysine-to-arginine mutation at codon 43 of rpsL (42,44). As a next step, the plasmid pcagA::cat-rpsL was generated by PCR amplification of a region extending from approximately 500 bp upstream of the cagA translational start site to 500 bp downstream of the cagA translational start site from H. pylori PZ5056 with primers 5=-GAAGCTGTCTTTGAAAATCTGTCC-3= and 5=-AATATCCAACCAATCCCCACCAG-3=.…”
Section: Methodsmentioning
confidence: 99%